2023
DOI: 10.1097/hrp.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

Co-Occurring Autism Spectrum and Borderline Personality Disorder: An Emerging Clinical Challenge Seeking Informed Interventions

Abstract: INITIAL CASE PRESENTATIONBrittany, a 21-year-old woman with borderline personality disorder (BPD), was referred to our specialist personality disorder service, with a presentation distinguished by high-lethality suicidal behaviors including ingestion of toxic substances and dangerous objects. She frequently ran to train stations and bridges. Brittany also engaged in daily cutting. Due to her high level of risk, she was increasingly restricted within her family home. She was not allowed into the backyard for fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…The co-occurrence, confusion, and misdiagnosis of personality disorder (PD) and autism spectrum disorder (ASD) have been increasingly investigated and discussed in recent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Both diagnoses are considered pervasive and persistent conditions, which affect all or most areas of psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-occurrence, confusion, and misdiagnosis of personality disorder (PD) and autism spectrum disorder (ASD) have been increasingly investigated and discussed in recent years [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Both diagnoses are considered pervasive and persistent conditions, which affect all or most areas of psychosocial functioning.…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule, when facing such issues with differential diagnosis, the ICD-11 points out that individuals with ASD should not be given an additional diagnosis of PD unless there are features of PD that cannot exclusively be accounted for by ASD and its co-occurring psychopathology such as eating disorder, OCD, non-suicidal self-injury, depression, or anxiety [ 17 ]. The question about the co-occurrence of PD and ASD also seems to be an emerging clinical challenge complicated by the introduction of a multi-axial system in DSM-III, in which the two diagnoses were allowed to co-occur [ 2 , 8 , 18 ]. In any case, as a neurodevelopmental disorder, the ICD-11 diagnosis of ASD generally overrules PD in the process of differential diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent scholars have called for increased attention to, and treatment of, comorbid ASD and BPD (Allely et al. , 2023; Cheney et al. , 2023; Dell’Osso et al.…”
mentioning
confidence: 99%
“…Furthermore, the hypersensitivity sometimes observed in ASD may act as the biological vulnerability to emotion that is described in Linehan's biosocial theory of BPD and subsequently increase the likelihood of encountering invalidation in interpersonal relationships (Baldwin and Costley, 2016). BPD has been called both an "outcome and an engine for adversity" (Cheney et al, 2023), with high rates of trauma exposure among patients (Golier et al, 2003). One study of women with ASD found that they are at higher risk for sexual victimization due to difficulties with social cues and assertiveness (Kanfiszer et al, 2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation